Aging and Work-Related Identity Loss Due to Retirement (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
Population aging in most developed countries and the associated aging of the workforce is an important and complex issue with far-reaching implications. Automatic adjustment mechanisms recently introduced in some EU Member States will raise the retirement age to 71 by 2060, meaning that work will occupy a large part of our lives. Work is closely linked to our identity. For many adults, a work-related identity is an important part of their personal identity. Although retirement is eagerly anticipated by many workers, it can lead to the loss of important work-related activities and social ties, which for some may affect stability and positive identity. This research aims to shed light on deeper psychological issues connected to work-related identity in the context of retirement. In particular, with a conducted literature review, this paper aims to offer a theoretical overview of work-related identity loss due to retirement. Findings reveal the importance of understanding work-related identity and the consequences of its loss. Results suggest that the transition and adjustment to retirement was particularly difficult for individuals with a strong work identity.